Measurement of the branching fractions of the decays B0s → D[bar]0K−π+ and B0 → D[bar]0K+π− - Aaij, Roel; Aquines Gutiérrez, Osvaldo; Bachmann, Sebastian; Bien, Alexander; Blouw, Johan; Britsch, Markward; Di Canto, Angelo; Dordei, Francesca; Färber, Christian; Fontana, Marianna; Gersabeck, Evelina; Grünberg, Oliver; et al. (Physical review. D, Particles, fields, gravitation, and cosmology, 2013)
The first observation of the decay B0s→D̄0K−π+ is reported. The analysis is based on a data sample, corresponding to an integrated luminosity of 1.0 fb−1 of pp collisions, collected with the LHCb detector. The branching fraction relative to that of the topologically similar decay B0→D̄0π+π− is measured to be B(B0s→D̄0K−π+)B(B0→D̄0π+π−)=1.18±0.05(stat)±0.12(syst). In addition, the relative branching fraction of the decay B0→D̄0K+π− is measured to be B(B0→D̄0K+π−)B(B0→D̄0π+π−)=0.106±0.007(stat)±0.008(syst).